Health conditions of inmates in Italy. (December 2016) - Voller, Fabio; Silvestri, Caterina; Martino, Gianrocco; Fanti, Eleonora; Bazzerla, Giorgio; Ferrari, Fabio; Grignani, Marco; Libianchi, Sandro; Pagano, Antonio; Scarpa, Franco; Stasi, Cristina; Di Fiandra, Teresa
Abstract Background Several studies have shown that prison is characterized by a higher prevalence of chronic diseases than unconfined settings. The aim of this study was to describe the characteristics and health of inmates, focusing on internal diseases. Methods We designed a specific clinical record using the Python programming language. We considered all of the diagnoses according to the ICD-9-CM. Results Of a total of 17, 086 inmates, 15, 751 were enrolled in our study (M = 14, 835; F = 869), corresponding to 92.2% of the entire inmate population (mean age of 39.6 years). The project involved a total of 57 detention facilities in six Italian regions (for a total of 28% of all detainees in Italy), as counted in a census taken on February 3, 2014. From the entire study sample, 32.5% of prisoners did not present any disorders, while 67.5% suffered from at least one disease. The most frequent pathologies were psychiatric (41.3%), digestive (14.5%), infectious (11.5%), cardiovascular (11.4%), endocrine, metabolic, and immune (8.6%), and respiratory (5.4%). Conclusion The findings showed that a large number of detainees were affected by several chronic conditions such as hypertension, dyslipidemia and type 2 diabetes mellitus, with an unusually high prevalence for such a young population. Therefore, a series of preventive measures is recommended to strengthen the entire care process and improve the health and living conditions of prisoners.